Clinical Characteristics of Auditory Mismatch Negativity in Patients with Chronic Disorders of Consciousness Following Intracerebral Haemorrhage: A Prognostic Prediction Study - Lv X; Yang N; Lv J; Li L; Gao Y; Xiang Z; Li Z; Lang X; Tao D; Zhao Y; Duan H; Li H (Journal of Multidisciplinary Healthcare, 2025)
Xuehai Lv,1,* Nuan Yang,2,* Jingwei Lv,3 Linxi Li,4 Yuemin Gao,5 Zhengmao Xiang,6 Zhengfan Li,4 Xiaoguang Lang,5 Dan Tao,7 Yuqin Zhao,5 Haili Duan,5 Hongling Li1 1Second Department of Rehabilitation Medicine, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei Province, 050000, People’s Republic of China; 2Graduate School, Hebei Medical University, Shijiazhuang, Hebei Province, 050017, People’s Republic of China; 3School of Basic Medicine, Hebei Medical University, Shijiazhuang, Hebei Province, 050017, People’s Republic of China; 4Graduate school, Hebei North University, Zhangjiakou, Hebei Province, 075000, People’s Republic of China; 5Department of Clinical Rehabilitation Medicine, Handan Central Hospital, Handan, Hebei Province, 056001, People’s Republic of China; 6Graduate school, Chengde Medical University, Chengde, Hebei Province, 067000, People’s Republic of China; 7Academy of Geography, Sociology, and International Studies, Hong Kong Baptist University, Hong Kong, 519000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongling Li, Second Department of Rehabilitation Medicine, The Second Hospital of Hebei Medical University, No. 215 of Hepingxi Road, Xinhua District, Shijiazhuang, Hebei Province, 050000, People’s Republic of China, Tel +86 15803210622, Email lihongling_lhl@163.comObjective: To examine the clinical features of auditory mismatch negativity (MMN) and its potential utility in prognostic prediction in patients with chronic disorders of consciousness (DOC) following intracerebral haemorrhage (ICH).Methods: Between September 2023 and July 2024, 24 patients with chronic DOC following ICH were recruited. The Coma Recovery Scale-Revised (CRS-R) was used to assess the patients’ level of consciousness, dividing them into vegetative state, minimally conscious state and escaped minimally conscious state groups. Auditory MMN data were collected from each group using an oddball paradigm, and differences in MMN amplitude and latency were compared. Follow-up was conducted 3 months later. Patients were categorised into favourable and unfavourable outcome groups based on the Glasgow Outcome Scale scores. The receiver operating characteristic curve method was utilised to evaluate the prognostic predictive power of significant indicators, establishing cut-off values.Results: The amplitude of auditory MMN was different in patients with varying levels of consciousness. The MMN amplitude at electrode Cz was associated with prognosis (P < 0.05), and the area under the curve was 0.850 (95% CI: 0.79– 0.91). Moreover, MMN amplitudes at Cz were dichotomised at a value of 1.19 μV, with a sensitivity and specificity of 87.5% and 80.0%, respectively, for the prognosis prediction. The prediction value improved when combined with the CRS-R and the Glasgow Coma Scale.Conclusion: Auditory MMN amplitude, particularly at electrode Cz, serves as a reliable prognostic indicator for patients with chronic DOC following ICH. Its integration with clinical scales enhances predictive accuracy, offering valuable insights for clinical decision-making and patient management.Keywords: chronic disorders of consciousness, auditory mismatch negativity, coma recovery scale-revised, Glasgow coma scale, prognosis, intracerebral haemorrhage